MORE THAN FOOTBALL: MEDIA COVERAGE ON SERBIAN TEAM IN WORLD CUP 2018. - Milinkov, Smiljana V; Strika, Zoran (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2019)
In this article, we are analyzing Serbian media coverage of the Football World Cup, held in Russia in 2018, and we explore the correlation between sports, politics and media in the process of shaping ideological and national discourse, as well as in spreading intolerance and hate towards others. Since this was a huge sports spectacle with important social and political significance on global and national level, since Serbian team participated after eight years of trying, the focus of the research was not on specialised sports media, but on the analysis of general interest news portals. The research was conducted using critical discourse analysis of the texts published on news portal of the public broadcaster Radio-television of Serbia (RTS), commercial media B92 and Informer and online edition of the traditional daily newspaper Politika. The results of analysis show that reporting of these media, when it comes to the Serbian team participation, was biased and emotionally charged, deprived of the professional journalistic distance, and as such this reporting can facilitate consolidation and expansion of national stereotypes about us and the others, which are dominant in discourse of political and intellectual elite.